Pathogenesis of Atopic Dermatitis: Current Paradigm - Furue, Masutaka; Ulzii, Dugarmaa; Vu, Yen Hai; Tsuji, Gaku; Kido-Nakahara, Makiko; Nakahara, Takeshi (Iranian journal of immunology, 2019)
Atopic dermatitis (AD) is characterized by skin inflammation, barrier dysfunction and chronic pruritus. In this review, recent advances in the pathogenesis of AD are summarized. Clinical efficacy of the anti-IL-4 receptor antibody dupilumab implies that type 2 cytokines IL-4 and IL-13 have pivotal roles in atopic inflammation. The expression of IL-4 and IL-13 as well as type 2 chemokines such as CCL17, CCL22 and CCL26 is increased in the lesional skin of AD. In addition, IL-4 and IL-13 down-regulate the expression of filaggrin in keratinocytes and exacerbate epidermal barrier dysfunction. Keratinocytes in barrier-disrupted epidermis produce large amounts of thymic stromal lymphopoietin, IL-25 and IL-33, conducing to type 2 immune deviation via OX40L/OX40 signaling. IL-31, produced by type 2 T cells, is a cardinal pruritogenic cytokine. IL-4 and IL-13 also amplify the IL-31-mediated sensory nerve signal. These molecules are particularly important targets for future drug development for AD.